2022
DOI: 10.3390/jpm12081327
|View full text |Cite
|
Sign up to set email alerts
|

What’s in a Name? Parents’ and Healthcare Professionals’ Preferred Terminology for Pathogenic Variants in Childhood Cancer Predisposition Genes

Abstract: Current literature/guidelines regarding the most appropriate term to communicate a cancer-related disease-causing germline variant in childhood cancer lack consensus. Guidelines also rarely address preferences of patients/families. We aimed to assess preferences of parents of children with cancer, genetics professionals, and pediatric oncologists towards terminology to describe a disease-causing germline variant in childhood cancer. Using semi-structured interviews we asked participants their most/least prefer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
(62 reference statements)
0
3
0
Order By: Relevance
“… 35 Our data speak to the important role of genetics education and repeated genetic counseling consultations, including at the time of consent and in the return of germline findings. 33 , 35 Education and training for clinicians, some of whom have previously described a lack of skills and confidence in communicating genomic results to families, 24 , 34 , 42 are also increasingly important with the continued uptake of genome sequencing in childhood cancer care.…”
Section: Discussionmentioning
confidence: 99%
“… 35 Our data speak to the important role of genetics education and repeated genetic counseling consultations, including at the time of consent and in the return of germline findings. 33 , 35 Education and training for clinicians, some of whom have previously described a lack of skills and confidence in communicating genomic results to families, 24 , 34 , 42 are also increasingly important with the continued uptake of genome sequencing in childhood cancer care.…”
Section: Discussionmentioning
confidence: 99%
“…It is crucial to convey this information in a manner that clients can comprehend easily, take appropriate action upon, and uses their preferred language. The articles in this Special Issue underscore the importance of achieving these objectives to ensure the adoption of desired behaviors [15,16]…”
Section: Communicating Complex Information To Clients and Their Famil...mentioning
confidence: 99%
“…It is crucial to convey this information in a manner that clients can comprehend easily, take appropriate action upon, and uses their preferred language. The articles in this Special Issue underscore the importance of achieving these objectives to ensure the adoption of desired behaviors [ 15 , 16 ]. The second link in the communication chain that Pedrazzani et al reported involves clients sharing their genetic information with family members.…”
Section: Communicating Complex Information To Clients and Their Famil...mentioning
confidence: 99%